2001
DOI: 10.1021/es010699o
|View full text |Cite
|
Sign up to set email alerts
|

Atmospherically Derived Organic Surface Films along an Urban-Rural Gradient

Abstract: Atmospherically derived organic films have been found on an impervious surface along an urban-rural gradient in the Toronto, Ontario, Canada area. Film thickness and concentrations, expressed on an aerial basis, of sigman-alkanes, sigmaPCB, sigmaPAH, and sigmaOC (organochlorine) pesticides decrease along this gradient, coincident with lower atmospheric emissions (PCB and PAH) and less accumulation in thinner rural films (OC pesticides). For PCBs and some OC pesticides, patterns of chemical abundance also shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
143
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(159 citation statements)
references
References 60 publications
(72 reference statements)
14
143
2
Order By: Relevance
“…In Hong Kong, the streets are generally narrow, and the buildings are close to the roadside; the higher contributions of BghiP suggest that the major source of PAHs on the window surfaces might be local vehicle emissions. Generally, the patterns of individual PAH concentrations in this study were consistent with those of previously reported film samples (Gingrich et al, 2001;Unger and Gustafsson, 2008). The concentration pattern at all sampling sites showed an increase in the predominantly light-weight PAHs (Flu, Phe, Flur, and Pyr) in comparison with urban air particulate samples as well as a greater abundance of heavy-weight PAHs, such as BbF, BkF, BaP, Ind, DahA, and BghiP, than in the total urban air (gas plus particle phases) .…”
Section: Pah Concentrations and Sources In Guangzhou And Hong Kongsupporting
confidence: 92%
See 3 more Smart Citations
“…In Hong Kong, the streets are generally narrow, and the buildings are close to the roadside; the higher contributions of BghiP suggest that the major source of PAHs on the window surfaces might be local vehicle emissions. Generally, the patterns of individual PAH concentrations in this study were consistent with those of previously reported film samples (Gingrich et al, 2001;Unger and Gustafsson, 2008). The concentration pattern at all sampling sites showed an increase in the predominantly light-weight PAHs (Flu, Phe, Flur, and Pyr) in comparison with urban air particulate samples as well as a greater abundance of heavy-weight PAHs, such as BbF, BkF, BaP, Ind, DahA, and BghiP, than in the total urban air (gas plus particle phases) .…”
Section: Pah Concentrations and Sources In Guangzhou And Hong Kongsupporting
confidence: 92%
“…Comparing the PAH concentrations measured in this study with the limited observations of PAH levels in glass films, the areanormalized PAH concentrations in Hong Kong and Guangzhou were much lower than those reported in downtown Toronto, Canada (Gingrich et al, 2001). PAH concentrations in Guangzhou were found to be similar to those in the suburban areas of Toronto, and the concentrations in Hong Kong were similar to those in the rural areas of Toronto (Gingrich et al, 2001).…”
Section: Pah Concentrations and Sources In Guangzhou And Hong Kongsupporting
confidence: 54%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] Airborne particles also have a complex composition, with organic compounds as major components. [8][9][10][11] The chemistry associated with particles is of major interest because they are known to have adverse impacts on climate, human health and the chemistry of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%